2011
DOI: 10.1111/j.1742-9536.2011.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

The stigma of having a parent with mental illness: Genetic attributions and associative stigma

Abstract: Children often report associative stigma because they are 'contaminated' by association with a parent who has a mental illness. An exploratory study was conducted to investigate the role of genetic attributions in the aetiology of associative stigma. The first hypothesis was that genetic attributions would predict associative stigma over and above the contribution of biochemical and stressful-event attributions, while the second hypothesis was that the relationship between genetic attributions and associative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…Most research on the effects of geneticization on family members of people with stigmatized disorders examines views of the public toward the relatives . In contrast, we examined felt stigma from the point of view of the family members themselves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most research on the effects of geneticization on family members of people with stigmatized disorders examines views of the public toward the relatives . In contrast, we examined felt stigma from the point of view of the family members themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Most research on the effects of geneticization on family members of people with stigmatized disorders examines views of the public toward the relatives. 16,17 In contrast, we examined felt stigma from the point of view of the family members themselves. We are aware of only one other study that has addressed this question in epilepsy: a study of mothers of children with epilepsy in Zambia, which found that 20% of the mothers felt stigmatized because of the child's epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Stigma is often associated with mental illness, and children who live with a parent with a mental illness are perceived by some to be "contaminated" by their parent. 17 One seminal study found that the direct effects of parental mental illness were less detrimental than the social adversity (such as unemployment, housing problems and isolation)…”
Section: Examining Mechanisms Of Risk Transmissionmentioning
confidence: 99%
“…For example, Koschade and Lynd-Stevenson (2011) propose that children with parental mental problems have to find ways to cope with their associative stigma; the old saying "like father like son" may insidiously affect the life of these children. Moreover, Gladstone, Boydell, and McKeever (2006) argue that being identified as "at risk" for a mental disorder is a powerful label for children.…”
mentioning
confidence: 99%